Phytosanitary Management of ICARDA’s Germplasm Seed Collections for Better Future Use - Kumari, Safaa; Moukahel, Abdulrahman; El Miziani, Inaam (The International Society for Plant Pathology, 2023)
Recent years have witnessed an increasing global concern about the loss of plant genetic resources, as a result of conflicts, epidemics, earthquakes, etc., which led to disrupting access to some germplasm and undermining social protection systems, and thus an increase in global awareness to preserve germplasm for their current and future use. This led genebanks all over the world to create disaster risk reduction policies to organize activities in the safekeeping, conservation, and dissemination of germplasm resources. Safety duplication of base collection at different geographic sites, such as Svalbard Global Seed Vault, is one of the essential measures. Any procedure must comply with phytosanitary regulations to enable direct and rapid response for safe germplasm exchange and retrieval. In order to make sure that germplasm is viable to combat challenges, ICARDA’s Germplasm Health Unit (GHU) exercises maximum effort to maintain the health status of germplasm collections, ensure compliance with phytosanitary regulations in international germplasm distributions, and develop methods to detect and manage seed-borne pathogens to guarantee minimum loss of genetic resources. In addition, maintaining plant health during germplasm regeneration is essential to reducing the risk of seed-borne pathogen spread via future germplasm distributions.